NEPHROLYSIS PATHOPHYSIOLOGY: MECHANISMS AND CLINICAL IMPLICATIONS - SHODIEV ULMAS MUSTAFOEVICH (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Nephrolysis is a surgical procedure involving the dissection of perinephric adhesions surrounding the kidney, often performed to treat obstructive uropathy or chronic flank pain caused by fibrosis. Although frequently successful, the underlying pathophysiological mechanisms leading to the need for nephrolysis—such as chronic inflammation, retroperitoneal fibrosis, and ischemia—are complex and multifactorial. This article explores the biological and molecular pathways that contribute to perinephric adhesion formation and reviews the clinical consequences and outcomes of nephrolysis.